Retinal nerve fiber layer thickness in Indian eyes with optical coherence tomography - Malik, A; Singh, M; Arya, SK; Sood, S; Ichhpujani, P (Nepalese Journal of Ophthalmology, 2012)
Introduction: Measuring the thickness of the retinal nerve fiber layer is a potential method of recognizing axon loss prior to the visual field abnormality. Objective: To study normal individuals to quantify peripapillary retinal nerve fiber layer (RNFL) thickness in Asian Indian subjects. Materials and methods: This was a prospective study of 150 normal subjects. Peripapillary RNFL was imaged with Optical Coherence Tomography (OCT3) and the thickness of the RNFL around the disc was determined in four quadrants with a 3.4 mm circle OCT scan. The influence of age and gender was evaluated on various parameters using unpaired t test, Pearson’s correlation coefficient and ANOVA. Results: The sample included 66 males and 84 females. The mean age of the study sample was 42.64 ± 13.63 years. The average RNFL thickness was 101.07 ± 10.13μm with the maximum thickness in the inferior quadrant (127.47±15.57) followed by the superior, nasal and temporal quadrants. The difference between the inferior and superior quadrants was statistically significant (p < 0.001). There was no significant difference in RNFL thickness between males and females. Negative correlation was found between age and average RNFL thickness, superior and temporal average (Pearson’s correlation value = -0.262, - 0.209, - 0.294 respectively and p = 0.02, 0.04, 0.001 respectively). Conclusion: The present study provides additional data on the existing database of RNFL thickness in Asian Indians. It is also evident that RNFL thickness decreases with age but there is no relationship with gender. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5852 NEPJOPH 2012; 4(1): 59-63